Intra-Abdominal Hypertension Syndrome in Patients with Acute Abdominal Pathology - Farida Azizova (International Journal of Medical Toxicology and Legal Medicine, 2024)
Intra-abdominal hypertension syndrome (IAH) is a critical complication in patients with acute abdominal pathology, significantly affecting prognosis and mortality rates. This study retrospectively analyzed 916 cases of emergency surgical conditions and abdominal trauma treated at the Republican Scientific Center for Emergency Medical Care, Uzbekistan (2021-2024). The incidence of increased intra-abdominal pressure (IAP) was observed in 35.9% of patients, with the condition more prevalent among males, elderly patients, and individuals with elevated BMI. Clinical severity, assessed using APACHE II and SOFA scales, was significantly higher in the IAH group, correlating with adverse outcomes such as multiple organ dysfunction and increased mortality. The findings highlight the necessity of early diagnosis, monitoring, and intensive management of IAH to mitigate complications and improve outcomes. Key predictive factors include BMI, gender, age, and comorbidities, with specific hemodynamic and respiratory parameters indicating the severity of IAH.